2019
DOI: 10.1037/fam0000504
|View full text |Cite
|
Sign up to set email alerts
|

Personal well-being across the transition to marriage equality: A longitudinal analysis.

Abstract: We examined the ways that federal, state, and local marriage recognition influence multiple domains of personal well-being of individuals in same-sex (n ϭ 279) and different-sex (n ϭ 266) relationships. Longitudinal data were collected across the transition to marriage equality (i.e., the U.S. Supreme Court Obergefell v. Hodges [2015] case decision, which resulted in same-sex marriage recognition federally). Prior to the ruling, levels of stigma and psychological distress were higher and family support was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 63 publications
(80 reference statements)
1
31
0
Order By: Relevance
“…Seventeen studies examined the impact of equal marriage rights on sexual minority individuals’ or couples’ relationships with their families of origin. Although these studies predominately used cross-sectional survey designs, one longitudinal study included individuals in both different-sex and same-sex relationships before and after the U.S. Supreme Court decision that extended marriage rights to all states [ 44 ]. This study found that support from family members increased following national legalization of same-sex marriage [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seventeen studies examined the impact of equal marriage rights on sexual minority individuals’ or couples’ relationships with their families of origin. Although these studies predominately used cross-sectional survey designs, one longitudinal study included individuals in both different-sex and same-sex relationships before and after the U.S. Supreme Court decision that extended marriage rights to all states [ 44 ]. This study found that support from family members increased following national legalization of same-sex marriage [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although search terms were inclusive of transgender individuals, samples in the studies we reviewed rarely included or focused explicitly on experiences of transgender or gender nonbinary identified individuals. In studies that explicitly included transgender and nonbinary individuals, sample sizes were rarely large enough to permit examination of differences based on gender identity (e.g., survey samples with 2-3% representation of nonbinary or transgender individuals) [44,[59][60][61][62][63]. Other studies recruiting sexual…”
Section: Selection Methodsmentioning
confidence: 99%
See 3 more Smart Citations